Physical Education for ALL in Colorado. (2nd January 2020) - McMullen, Jaimie M.; Rogers, Pam
Abstract : The benefits of quality physical education are well documented, and include improvements in physical literacy, fitness, concentration and psychological and emotional benefits. However, physical education continues to be a marginalized subject. This article describes how the Society of Health and Physical Educators - SHAPE Colorado has put more emphasis on advocacy efforts (e.g., website content, lobby days), and what the lasting impact may be.